Turks and Other Muslims in the US: An Analysis of Perceptions - Karataş, İbrahim (Journal of Al-Tamaddun, 2021)
Surveys show that, in the United States, Americans have a less favorable view of Muslims due to various reasons as opposed to American Muslims who conversely favor the American state and population. In line with this fact, this study tries to understand whether the Turkish community living in the US has different views about Americans than American Muslims do. This study makes a comparison because not all ethnic groups in the American Muslim community have the same views about Americans. While analyzing the Turkish community’s perceptions, this study also analyzes the views Americans and Muslim Americans have towards each other. The study compares previous surveys with the survey conducted among Turks living in the US and concludes that Muslims generally have the same perceptions regarding Americans. It also reveals that aside from the basic reasons which result in a negative view towards Muslims, being a small community and fragmented are two significant factors that damage the image of Muslims. In addition, it reveals that a lack of knowledge about each other increases negative perceptions.